Hospitalization of childhood rotavirus infection from Kuala Lumpur, Malaysia - Lee, Way Seah; Veerasingam, P.D.; Goh, A.Y.T.; Chua, K.B. (Wiley, 2003)
Aim: To determine the epidemiology of rotavirus gastroenteritis in children admitted to an urban hospital in a developing country from South-East Asia. Methods: Retrospective review of cases of acute gastroenteritis admitted to the children's ward of the University of Malaya Medical Centre, Kuala Lumpur, Malaysia, between 1996 and 1999. Results: During the study period, 333 cases (24) of 1362 stool samples, obtained from children admitted with acute diarrhoea, were positive for rotavirus. Acute gastroenteritis constituted 8.2, and rotavirus infection 1.6 of all the paediatric admissions each year. Of the 271 cases analysed, 72 of the affected population were less than 2 years of age. Peak incidence of admissions was between January to March, and September to October. Dehydration was common (92) but electrolyte disturbances, lactose intolerance (5.2), prolonged diarrhoea (2.6) and cow's milk protein intolerance was uncommon. No deaths were recorded. Conclusions: Rotavirus infection was a common cause of childhood diarrhoea that required hospital admission in an urban setting in Malaysia.